1996
DOI: 10.3354/meps134299
|View full text |Cite
|
Sign up to set email alerts
|

Modelling coral reef biodiversity and habitat destruction

Abstract: World wide coral reef decline has now been well nities, species have been understood to interact in a documented, but the actual dynamics of this disturbing phehierarchical web of competitive interactions, In all of nomenon are still far from understood. In t h~s note we the above models, a set of N species colonize and com- Coral reefs, the most complex and diverse of all aquatic ecosystems, are currently facing widespread devastation. Wilkinson (1993) warned that some 70% of the world's reefs will be comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 4 publications
0
18
0
Order By: Relevance
“…Stone (99,100) analyzed a Red Sea reef flat and concluded that numbers of species extinctions associated with habitat reduction would be especially catastrophic because competitively dominant corals were already rare. However, this result reflects the fact that reef flats are regularly disturbed and, thus, always dominated by weedy corals.…”
Section: Threshold Effects Multiple Stable States and Metapopulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Stone (99,100) analyzed a Red Sea reef flat and concluded that numbers of species extinctions associated with habitat reduction would be especially catastrophic because competitively dominant corals were already rare. However, this result reflects the fact that reef flats are regularly disturbed and, thus, always dominated by weedy corals.…”
Section: Threshold Effects Multiple Stable States and Metapopulationsmentioning
confidence: 99%
“…The models (97,98), as they have been applied to reefs to date (99,100), assume that each patch is occupied by a single species. In this sense, the analyses describe the dynamics on single reefs, with patches being de facto the spaces occupied by individual colonies.…”
Section: Threshold Effects Multiple Stable States and Metapopulationsmentioning
confidence: 99%
“…Caswell & Cohen 1993, Tilman et al 1994, Man et al 1995, Stone et al 1996 assume th.at disturba.nce leads to complete extinction of species on a patch but, during ecological time scales, such severe effects of disturbance are not appropriate for open populations of marine organisms which may show greater resistance to extinction (Caley et al 1996, Connell et al 1997. A more suitable model would allow local populations to be depressed but rarely driven to extinction.…”
Section: Coral Growth and Mortalitymentioning
confidence: 99%
“…Iwasa . Man et al 1995, Stone et al 1996). An appropriate model of larval dispersal needs 2 principal components: (1) the geographic transport of larvae between reefs, which depends on the velocity and vertical stratification of oceanic and coastal currents, and the motility of larvae, and (2) the survivorship of larvae over time.…”
Section: The Planktonic Component Of the Metapopulation Modelmentioning
confidence: 99%
See 1 more Smart Citation